AgCl-induced hot salt stress corrosion cracking in a titanium alloy. (15th July 2021) - Shi, Yitong; Joseph, Sudha; Saunders, Edward A.; Sandala, Rebecca S.; Walker, Adrian; Lindley, Trevor C.; Dye, David
Highlights: AgCl-induced stress corrosion cracking of Ti-6246 was examined at 500 MPa/380 °C/24 h. SEM and STEM-EDX showed that metallic Ag migrated along the crack. TEM analysis also revealed the presence of SnO2 and Al2 O3 corrosion products mixed into TiO2 . Long, straight, dislocations were observed in a facetted primary alpha grain at the surface. Abstract: The mechanism of AgCl-induced stress corrosion cracking of Ti-6246 was examined at 500 MPa and 380 °C for 24 h exposures. SEM and STEM-EDX examination of a FIB-sectioned blister and crack showed that metallic Ag was formed and migrated along the crack. TEM analysis also revealed the presence of SnO2 and Al2 O3 corrosion products mixed into TiO2 . The fracture surface has a transgranular nature with a brittle appearance in the primary α phase. Long, straight and non-interacting dislocations were observed in a brittle appearance fractured primary α grain, with basal and pyramidal traces. This is consistent with a dislocation emission view of the cracking mechanism.